Effect of irradiation on lipid characteristic of plant nuts - Anwar Ahmad Sattar; Altaf Hussain; Mohammad Zafar Iqbal (Universiti Kebangsaan Malaysia, 1997)
Different plant nuts were irradiated with gamma rays to dose levels of 0.5, 1.0 and 1.5 kGy. Total lipids of the treated and untreated samples of plant nuts such as almond, peanut, pinenut, walnut and stones of apricot were extracted with petroleum benzene. The esterified lipids were analyzed for their fatty acid composition by gas chromatography (CC) whereas the extracted oils were tested for other physical characteristics like peroxide, iodine, anisidine and free fatty acid (FFA) values. The cc analysis showed that irradiation treatment of 1.5 kGy exhibited almost negligible effect on the composition of fatty acids. The peroxide, anisidine and FFA values were higher in the irradiated samples than untreated controls. It was also observed that these effects were increased by increasing the irradiation dose from 0.5 to 1.5 kGy but a reverse trend was noted in the case of iodine value in each case.